If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(z + 2) + -2(2z + 5) = 18 Reorder the terms: 2(2 + z) + -2(2z + 5) = 18 (2 * 2 + z * 2) + -2(2z + 5) = 18 (4 + 2z) + -2(2z + 5) = 18 Reorder the terms: 4 + 2z + -2(5 + 2z) = 18 4 + 2z + (5 * -2 + 2z * -2) = 18 4 + 2z + (-10 + -4z) = 18 Reorder the terms: 4 + -10 + 2z + -4z = 18 Combine like terms: 4 + -10 = -6 -6 + 2z + -4z = 18 Combine like terms: 2z + -4z = -2z -6 + -2z = 18 Solving -6 + -2z = 18 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -2z = 18 + 6 Combine like terms: -6 + 6 = 0 0 + -2z = 18 + 6 -2z = 18 + 6 Combine like terms: 18 + 6 = 24 -2z = 24 Divide each side by '-2'. z = -12 Simplifying z = -12
| -8=4(x-3) | | 122-(6x+7)=6(x+4)+x | | 8x+41=-9(x+3) | | 7x+1-6x=-4 | | -3=5/6x+4 | | 4x^2+3x-612=0 | | 4n+2(2n-1)=14 | | 7b-0.5=2b+4.5 | | 5n+2=42 | | 4-2x+6x=48 | | 9(w-7)=3+8w | | 4y=-12x-36 | | 3-p+11p=7(6+7p)+8(-8-8p) | | 23=4x+4x+7 | | 3x+3(x+2)=24 | | r=3x+14 | | 2345678763456789098643212121212345678987654321+6789=Z | | (-4-6i)+(i)-(2i)= | | 5(1r-1)=2(1r-4)-6 | | 2x+10-6x=-30 | | -X-90=50-4X | | -17-3= | | 3/6-x=2 | | -30=5(2x-2)-6x | | 6=k/9 | | 4x+9+5x=108 | | 16h=8(2h+(-10)) | | c/4+1=8 | | 96=80+r | | X+(x+0.15)p+(p+0.15)=40 | | -9(6+h)=2h-10 | | 3=x-2x+3 |